Social and Professional Impact of Learning Communities Within the Alliances for Graduate Education and the Professoriate Program at Michigan State University - Thomas, Steven D.; Ali, Abdifatah; Alcover, Karl; Augustin, Dukernse; Wilson, Neco (Frontiers in Psychology, 2021)
At Michigan State University (MSU), the AGEP learning community features the participation of over 70 % of the African-American, Latinx, and Native-American (under-represented minorities, URM) also referred to as Black, Indigenous, and People of Color (BiPOC) doctoral students in fields sponsored by the National Science Foundation (NSF). Monthly Learning Community (LC) meetings allow AGEP participants to create dialogues across disciplines through informal oral presentations about current research. The learning communities also offer opportunities to share key information regarding graduate school success and experience; thus providing a social network that extends beyond the academic setting. At MSU, AGEP also provides an interdisciplinary and multigenerational environment that includes graduate students, faculty members, post-docs and prospective graduate students. Using monthly surveys over a 4-year period, we evaluated the impact of this AGEP initiative focusing on the utility of the program, perceptions of departmental climate, career plans and institutional support. Findings indicate that AGEP participants consider their experiences in the program as vital elements in the development of their professional identity, psychological safety, and career readiness. Experiences that were identified included networking across departments, focus on career placement, involvement in minority recruitment and professional development opportunities. Additionally, AGEP community participants resonated with the "sense of community" that is at the core of the MSU AGEP program legacy. In this paper, we proposed a variation of Tomlinson’s Graduate Student Capital model to describe the AGEP participants’ perceptions and experiences in MSU AGEP. Within this four-year period, we report over 70% graduation rate (completing with advanced degrees). More than half of PhD students and almost 30% of master’s degree students decided to pursue academia as their careers. In addition, we found a high satisfaction rate of AGEP among the participants. Our analysis on graduate student capital helped us identify motivating capital development by years spent at MSU and as an AGEP member. These findings may provide some insight into which capitals may be deemed important for students relative to their experiences at MSU and in AGEP and how their priorities change as they transition towards graduation.